Tax Avoidance in the Form of Base Erosion and Profit Shifting in Digital Economic Transactions by Multinational Companies - Ricky Apriadi; Lita Monalysa (Sekolah Tinggi Ekonomi dan Bisnis Islam Lampung, 2021)
Google, recently has received some attention from the Indonesian government regarding tax avoidance. The attentions occur for major profit Google has gained through commercial, without tax contribution to Indonesia, is deemed to be unethical and unfair. Google as a company, receives income and utilizes public facilities in Indonesia, but shifts the income it earns in Indonesia into Singapore, so to speak it commits tax avoidance. The scheme of tax avoidance that Google has managed can also be termed as profit shifting. Profit shifting strategy itself may cause a decrease in tax earnings, hence becoming a threat for Indonesian base erosion. The main focus of this study is the tax avoidance scheme by Google, inhibiting factors of government policy against tax avoidance, and the government's strategy to face the tax avoidance. Data sources for this research are obtained from books, internet articles, and relevant constitutional regulations. The result from the study indicates Google has demonstrated tax avoidance in Indonesia by displacing its earnings to Singapore using the Double Irish Dutch Sandwich scheme. In addition, the Indonesian government faces several problems concerning its policy against tax avoidance, since Google does not own a permanent establishment in the country mentioned, accordingly it is difficult for the government to collect acquired tax payable that Google should have been compensated. The recommendation in this study for the government is to establish tax regulation dealing digital economy across jurisdictions or countries for multinational companies, or over the top.